1993
DOI: 10.1203/00006450-199312000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) Serum Levels and Apolipoprotein(a) Phenotypes in Children with Chronic Renal Disease

Abstract: ABSTRACT. Lipoprotein(a) [Lp(a)] has recently beenLp(a) is a cholesterol-rich lipoprotein resembling LDL, but characterized as a genetically determined risk factor for with a different protein composition, consisting of apo B-100 atherosclerosis and thrombosis. Normally, Lp(a) serum and apo(a). Increased blood concentrations of Lda) are strongly levels are closely related to the apo(a) phenotype. We associated with an increased risk for atherosclerosis (8-10) and studied Lp(a) serum levels and apo(a) phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
1
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 15 publications
2
19
1
3
Order By: Relevance
“…Further, a mild glomerular filtration rate impair ment was associated with a higher Lp(a) level in a recent study of diabetic patients (172). In other studies, however, Lp(a) concentrations did not differ from those of controls (173)(174)(175)(176)(177). In a large multicenter study, Kronenberg et al (145) reported higher Lp(a) levels in patients undergoing continuous ambulatory peritoneal dialysis compared with HD.…”
Section: Kidney Diseasementioning
confidence: 91%
“…Further, a mild glomerular filtration rate impair ment was associated with a higher Lp(a) level in a recent study of diabetic patients (172). In other studies, however, Lp(a) concentrations did not differ from those of controls (173)(174)(175)(176)(177). In a large multicenter study, Kronenberg et al (145) reported higher Lp(a) levels in patients undergoing continuous ambulatory peritoneal dialysis compared with HD.…”
Section: Kidney Diseasementioning
confidence: 91%
“…were still higher at 6 months of remission compared with levels previously reported for children 14,15 and by reference to an age-matched control population of children composed of 109 boys and 91 girls.…”
Section: Plasminogen and Apo(a)/lp(a) Quantificationmentioning
confidence: 60%
“…5,51 Marked lipid abnormalities, such as elevation of lipoproteins containing apo B, ie, VLDL, LDL, and Lp(a), have been previously reported 52 and were confirmed by results of the present studies. Nephrotic children have significantly higher plasma concentrations of Lp(a) than do healthy children 14,15,[53][54][55][56] ; these high levels of Lp(a) are an abnormality currently considered to be an independent risk factor for the development of cardiovascular disease in the general population. 18 The mechanism by which Lp(a) may favor the atherothrombotic process may be related to the lysine-binding properties of apo(a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations